CHALLENGES AND OPPORTUNITIES IN IMPLEMENTING GLOBAL HOUSEKEEPING STANDARDS AT THE GRAND PRINCE HOTEL OSAKA BAY, JAPAN - Aldi, Aldi; Adiatma, Dani; Rukma, Deden Firman Syuyaman; Dhamayanty, Stanny (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
The integration of foreign interns in the Japanese hospitality industry, particularly in housekeeping operations, presents various challenges and opportunities. This study examines the adaptation process of foreign interns at Grand Prince Hotel Osaka Bay, focusing on language barriers, cultural differences, and operational efficiency. Using a qualitative approach, data was collected through observations and interviews with foreign interns and hotel staff. The findings indicate that language barriers and cultural adaptation significantly impact the performance of foreign interns. However, structured training programs, mentorship initiatives, and technological interventions have proven to enhance their integration. While global housekeeping standards align with Japanese hospitality practices, discrepancies in service responsiveness during peak seasons highlight the need for resource optimization. The study underscores the necessity of balancing rigorous housekeeping standards with flexible adaptation programs to accommodate international staff. Future research should explore long-term adaptation strategies and examine cross-cultural workforce integration in multiple hospitality settings to provide broader insights into effective global workforce management.